Evaluasi Kekesatan Runway Menggunakan MuMeter Run Report (Studi Kasus : Bandar Udara Budiarto – Curug) - Ika Endrawijaya; Wahyu Dwi Agustini; Tiara Nugrahayani; Risqi Wahyu Jati Utama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Budiarto Airport has a runway, taxiway, and apron with flexible pavement and a PCN of 37 F/C/X/T. Flexible pavement is elastic, in this case asphalt, while rigid pavement uses concrete and is more rigid. With the increase in aircraft movements, an evaluation of the runway pavement condition using the Pavement Condition Index (PCI) is necessary to determine the condition of the pavement surface. PCI is a visual test that assists in the maintenance and repair of pavements when necessary. The results of the PCI survey of Runway 12-30 at Budiarto Airport were 99.10, which is classified as “good,” indicating that the runway pavement surface is still in good functional condition. This is one of the safety factors in aviation, namely the condition of the runway. The more aircraft that operate, the more rubber deposits accumulate on the runway. This causes the runway to become slippery, which can cause aircraft to skid because the brakes cannot work effectively. To avoid the risk of accidents, regular checks of runway skid resistance are necessary. There are several methods that can be used to check the condition of runway friction, one of which is using a MuMeter device. Based on the tests that have been carried out and based on Government Decree No. 94 of 2015 in classifying the damage and roughness experienced on the runway at Budiarto Airport, recommendations for handling the Budiarto runway can be obtained, namely “Major Rehabilitation (overlay or similar methods)”.